EDWARD SAPIR AND HIS CONTRIBUTION TO THE LINGUISTIC ETHNOGRAPHY. - Yuldasheva Dilshoda Musayevna (Western European Studies, 2024)
This article discusses the issue of cognitive-orientative and communicative-orientative ethno linguistics. The ideas and views of the American scientist, linguist, anthropologist Edward Sapir on ethnographic linguistics are also discussed. Various examples of ethno cultures are given and compared with each other. Besides the article open up the epic perspective by considering the experiential, aesthetic, emotional, moral and ethical value people bring while communicating with each other.
Keywords: Cognitive; ethno linguistics; perspective; cognitive issues